Concealing Untrustworthiness: The Role of Conflict Monitoring in a Social Deception Task - Hein, Fee-Elisabeth; Leue, Anja (Frontiers in Psychology, 2021)
Deception studies emphasize the important role of event-related potentials (ERPs) to uncover deceptive behavior based on underlying neuro-cognitive processes. The role of conflict monitoring as indicated by the frontal N2 component during truthful and deceptive responses was investigated in an adapted Concealed Information Test (CIT). Previously memorized pictures of faces should either be indicated as truthfully trustworthy, truthfully untrustworthy or trustworthy while concealing the actual untrustworthiness (probe). Mean, baseline-to-peak and peak-to-peak amplitudes were calculated to examine the robustness of ERP findings across varying quantification techniques. Data of 30 participants (15 female; age: M = 23.73 years, SD = 4.09) revealed longer response times and lower correct rates for deceptive responses. The frontal N2 amplitude was more negative for probe and truthfully untrustworthy compared to truthfully trustworthy stimuli when measured as mean or baseline-to-peak amplitude. Results suggest that deception evokes conflict monitoring and ERP quantifications are differentially sensitive to a-priori hypotheses.